Role of PET/CT for precision medicine in lung cancer: perspective of the Society of Nuclear Medicine and Molecular Imaging - Greenspan, Bennett S. (Translational Lung Cancer Research; Vol 6, No 6 (December 16, 2017): Translational Lung Cancer Research (Imaging- and blood-based biomarkers for lung cancer precision medicine), 2017)
This article discusses the role of PET/CT in contributing to precision medicine in lung cancer, and provides the perspective of the Society of Nuclear Medicine and Molecular Imaging (SNMMI) on this process. The mission and vision of SNMMI are listed, along with the guidance provided by SNMMI to promote best practice in precision medicine. Basic principles of PET/CT are presented. An overview of the use of PET/CT imaging in lung cancer is discussed. In lung cancer patients, PET/CT is vitally important for optimal patient management. PET/CT is essential in determining staging and re-staging of disease, detecting recurrent or residual disease, evaluating response to therapy, and providing prognostic information. PET/CT is also critically important in radiation therapy planning by determining the extent of active disease, including an assessment of functional tumor volume. The current approach in tumor imaging is a significant advance over conventional imaging. However, recent advances suggest that therapeutic response criteria in the near future will be based on metabolic characteristics and will include the evaluation of biologic characteristics of tumors to further enhance the effectiveness of precision medicine in lung cancer, producing improved patient outcomes with less morbidity.